DEADLINES OPTIMAL CORRECTION OF PROJECT EXECUTION FOR ANY DEVIATIONS FROM NETWORK SCHEDULE - Yu. I. Buryak; I. B. Ivenin; A. А. Skrynnikov (Научный вестник МГТУ ГА)
An algorithm of optimal correction of the work plan in the event of a deviation from the network schedule is proposed. Requirement within to perform activities in a given period of time with minimal additional resources involved to accelerate the work. The correction algorithm is based on using dynamic programming method taking into account the problem inherent feature when calculating the target function.